PERSPECTIVE OF ENERGY STORAGE IMPLEMENTATION IN TRACTION RAIL TRANSPORT (Transport systems and technologies, 2018)
The review and analysis of the energy efficiency research of traction rail transport through the use of energy storage. The basic directions of traction rail transport with energy storages are determined. According to the generalized analysis results of a significant amount of research is estimated the possible amount of savings resources through the implementation of energy storage on different types of rail traction transport. It is established that the most effective use of energy storage can be achieved on a city electric transport, especially in the metro. The main advantage of the use of energy storage in the metro is rolling stock operation feature. A set of tasks is formulated that can be solved in the subway through the implementation of energy storage. The basic lesser known and urgent tasks in solving the problem of energy efficiency in the metro through the application of energy storage, including the creation and modernization of metro rolling stock are determined.
Keywords: traction rail transport, energy storage, metro rolling stock, energy efficiency